2024
DOI: 10.21203/rs.3.rs-3910702/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic Profiling of Insecticide Resistance in Malaria Vectors: Insights into Molecular Mechanisms.

Victoria Ingham,
Sanjay Nagi

Abstract: Malaria control faces challenges from widespread insecticide resistance in major Anopheles species. This study, employing a cross-species approach, integrates RNA-Sequencing, whole-genome sequencing, and microarray data to elucidate drivers of insecticide resistance in Anopheles gambiae complex and An. funestus. Findings show an inverse relationship between genetic diversity and gene expression, with highly expressed genes experiencing stronger purifying selection. These genes cluster physically in the genome,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…As with Cyp4h17, Gstd3 was also highlighted as consistently differentially expressed in resistant field populations compared to laboratory colonies in a transcriptomic meta-analysis (Ingham and Nagi, 2024), and we further showed equivocal evidence of an association of copy number of this gene with resistance to deltamethrin in our data. Further evidence is needed to determine the importance of this gene in resistance, and the insecticides to which resistance is most strongly conferred.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…As with Cyp4h17, Gstd3 was also highlighted as consistently differentially expressed in resistant field populations compared to laboratory colonies in a transcriptomic meta-analysis (Ingham and Nagi, 2024), and we further showed equivocal evidence of an association of copy number of this gene with resistance to deltamethrin in our data. Further evidence is needed to determine the importance of this gene in resistance, and the insecticides to which resistance is most strongly conferred.…”
Section: Discussionmentioning
confidence: 49%
“…We ran simulations assuming that presence / absence of the CNV provided a similar effect size of resistance as was previously found in An. gambiae from Ghana (Nagi et al, 2024) and found that we had 88% power to detect the effect in our data.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations